AN ANALYSIS ON VALIDITY AND RELIABILITY OF TEST ITEMS IN PRE-NATIONAL EXAMINATION TEST SMPN 14 PONTIANAK - Pradana, Hanny; Sutapa, Gatot; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe main objective of this research is to find out whether the test items made by the teachers of SMPN 14 Pontianak were already valid and reliable especially for pre-national examination test. This test was analyzed by case study research with documentary study. The  test  items  used  as  the  sample  was  English  test in pre-national examination test designed by teachers of SMPN 14 Pontianak.  The study analyzed pre-national examination test which consist of 50 test items with a total participant of 344 students. The findings were divided into three parts: the appropriateness of test items with the principle of test construction, the validity and the reliability. For the appropriateness of the test items with the principle, the test did not fulfill the principle because the test items were constructed without test indicator. In content validity, the test items also did not show the specific learning purpose of the material being tested. However, the test score reliability calculated using by K-R20 was 0.798, which means the test was categorized as reliable and good to use as diagnostic test. Finally, the researcher recommended the teachers to revise the test items especially errors on item difficulty, item discrimination and distractor analysis.Keywords:Pre-National Examination Test, Test Item Analysis, Validity, Reliability, Junior High School, Pontianak Regency